2 plus 2 = 5: The Canadian Patent Agent Examination Board and the Doctrine of Essential Elements - Aoun, Wissam (2017)
Tremendous confusion has revolved around the theory and application of the doctrine of essential elements in Canadian patent law ever since the Supreme Court of Canada first introduced the doctrine in Free World Trust c. Électro Santé Inc. In recent years, the Canadian Intellectual Property Office’s (CIPO) interpretation and application of the doctrine in its patent application examination guidelines has been the subject of considerable criticism from the Canadian patent profession. However, CIPO’s misapplication of the doctrine in recent years’ Patent Agent Qualifying Examination has received relatively little attention. This paper examines the application of the doctrine of essential elements in recent years’ Canadian Patent Agent Qualifying Examination. The analysis begins with a thorough and comprehensive review of the doctrine of essential elements under Canadian patent law. The analysis reviews the last ten years’ Canadian Patent Agent Examination, with a focus on recent years’ emphasis on the doctrine of essentiality. Despite the fact that the doctrine itself is still unsettled under Canadian law, the approach taken on recent years’ Patent Agent Exams is at best an ambiguous, and at worst an inaccurate application of the doctrine. This paper concludes by demonstrating that the concerns surrounding the doctrine of essentiality may be significant contributing factor to invalidity issues surrounding recent years’ Patent Agent Exams.
Keywords: Wissam Aoun